Giant single molecule chemistry events observed from a tetrachloroaurate(III) embedded Mycobacterium smegmatis porin A nanopore - Jiao Cao (Nature Portfolio, 2019)
Engineered biological nanopores enable observation of single molecule chemistry events; however a cylindrical pore geometry can have undesired effects. The authors report a conical biological pore which was embedded with tetrachloroaurate(III) to allow for discrimination between different biothiols.